2021
DOI: 10.1021/acsapm.0c01306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response of Polymer Epoxy/BMI Composites with Graphene and a Boron Nitride Monolayer from First Principles

Abstract: Polymer composites possess an integrated combination of structures and properties associated with the host matrix and the fiber material and thus hold the potential of being high-strength materials. In general, the load transfer from the matrix to the fiber depends upon the strength of bonding at the interface, which characterizes the mechanical strength. In this work, first-principles calculations based on the density functional theory are employed to provide the molecular-level description of the interface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Overall, we find that the stacking configuration with the BMI component, A (i.e., BDM) interacting with graphene facilitates the energetically preferred configuration. This preferential stacking of ACB (or ABC) on graphene can be understood in terms of the effective area of contact at the interface. In the present work, the effective area of contact is calculated using the estimated length and width of the surface covered by a component using its distance of one end to the other in both x- and y -directions.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we find that the stacking configuration with the BMI component, A (i.e., BDM) interacting with graphene facilitates the energetically preferred configuration. This preferential stacking of ACB (or ABC) on graphene can be understood in terms of the effective area of contact at the interface. In the present work, the effective area of contact is calculated using the estimated length and width of the surface covered by a component using its distance of one end to the other in both x- and y -directions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…By applying periodic boundaries to the simulations, the influence of bulk environments could be included using MD simulations, thereby improving the rigor and realism of a model. The structural configurations of BMI components were obtained using the state-of-the-art first-principles method as described in Sachdeva et al and are listed in Table S5. The reactive force field ReaxFF with the parametrizations of Liu et al as implemented in the Large-scale Atomic/Molecular Massively Parallel Simulator program (LAMMPS) was used for the MD calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Periodic boundary conditions (PBC) modeling in polymer composites is of great importance, especially for graphene-polymer composite systems aimed at innovative applications, especially EMI shielding in our case. For graphene systems, we recommend the boundary conditions as per available literature, 3D periodic boundary conditions could be used for two-unit cells along with a four-atom-cluster as well as a 32-atom-cluster [73][74][75][76]. However, reports partnering to graphene-polymer a composite system have reportedly utilized 32, 162, etc.…”
Section: Band Gap Band Structures and Atom Projected Density States O...mentioning
confidence: 99%
“…C-atom supercells for graphene along with a vacuum value ranging from 20 Å, 30Å, etc. aimed at omitting the interfaces between the adjacent supercell images [73][74][75][76]. The periodic boundary condition may be chosen as per the property aim at by the researchers in the DFT study: diverse graphene supercells comprising of C-atoms for PBC have been reported [73][74][75][76].…”
Section: Band Gap Band Structures and Atom Projected Density States O...mentioning
confidence: 99%
See 1 more Smart Citation